Effectiveness of tyre chips as alternative material in vertical gabion wall to mitigate slope failure - Amir Zu Shafiq, Ab Hafiz (2018)
In order to reduce stockpiling of waste tyre by use it as a replacement material for gabion walls, the effectiveness of the replacement must be investigated. The main objectives of this study were to investigate the strength characteristic of gabion wall made from gravel mixed with tyre chips. Series of test using a slope and gabion walls model with artificial rainfall were conducted. The gabion walls were arranged in vertical order. A 60° slope without any retaining wall or support was tested first. The slope failed when subjected to 570mm/hr rainfall after two minutes. 100% of gravel and 100% tyre chips gabion walls placed and stacked in vertical order at the slope in separate test. There was no displacement of gabion wall detected. This means 100% tyre chips already provide sufficient support to prevent from slope failure happen. To ensure the truth of 100% tyre chips gabion walls can provide sufficient support, 50% gravel and 50% tyre chips gabion walls was tested at the same slope dimension. There was also no displacement occur after subjected to rainfall. Because of that, it can be concluded that replacing gravel with waste tyre as a material in gabion wall can be applied in a small scale project.